2018
DOI: 10.3341/kjo.2017.0105
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Outcomes of Combined Phacoemulsification and Ahmed Glaucoma Valve Implantation

Abstract: PurposeTo evaluate outcomes and factors associated with surgical failure in patients who underwent combined phacoemulsification and Ahmed glaucoma valve (AGV) implantation.MethodsThis retrospective and longitudinal study enrolled 40 eyes (38 patients) that underwent combined phacoemulsification and AGV implantation. Visual acuity, intraocular pressure (IOP), and number of antiglaucoma medications were evaluated preoperatively and postoperatively. Complete success was defined as a last follow-up IOP of 6 to 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
6
1
Order By: Relevance
“…A biometry prediction error within −1D and +0.5D was achieved in 63% patients, slightly higher than the 57% reported by Kwon and Sung with cataract surgery combined with AGV implantation 8 and slightly lower than the 74% reported by Tzu et al with combined cataract and glaucoma surgery. 4 …”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…A biometry prediction error within −1D and +0.5D was achieved in 63% patients, slightly higher than the 57% reported by Kwon and Sung with cataract surgery combined with AGV implantation 8 and slightly lower than the 74% reported by Tzu et al with combined cataract and glaucoma surgery. 4 …”
Section: Discussioncontrasting
confidence: 54%
“…14 Within ±0.5D, the biometry prediction error was 53.1% (26/49), higher than the 48.4% reported by Kang et al with cataract surgery with endoscopic cyclophotocoagulation, 15 but lower than the 59.7% reported by Manoharan et al with cataract surgery of glaucoma patients (without glaucoma surgery) 10 and the 72.7% reported by EUREQUO with standard cataract surgery. 14 A biometry prediction error within −1D and +0.5D was achieved in 63% patients, slightly higher than the 57% reported by Kwon and Sung with cataract surgery combined with AGV implantation 8 and slightly lower than the 74% reported by Tzu et al with combined cataract and glaucoma surgery. 4 To our knowledge, this is the first study to document the effects of tube position on the biometric predictability of cataract surgery combined with AGV implantation.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Although it was not statistically different, baseline IOP and number of medications were slightly lower in patients who underwent AGV + CEIOL surgery, which may account for differences in treatment response in the postoperative subgroup analysis. Retrospective studies have found that AGV + CEIOL surgery reduces IOP and number of medications after surgery 20,21. To our knowledge, there have been no comparative studies between AGV surgery alone vs combined AGV + CEIOL insertion.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the incidence of iris touch was 45.0% (9/20) in the group with no history of phaco, 12.5% (1/8) in the group with phaco, and 17.1% (6/35) in the group with a history of phaco (Table 6 ). The contact between the tube and iris may also cause inflammation, and Kwon et al reported that tube-iris touch is a risk factor with an 8.615 hazard ratio in Ahmed glaucoma valve implantation combined with phaco 21 . The tube should be carefully inserted to avoid touching the iris, and further investigation about the effect of tube-iris touch is needed.…”
Section: Discussionmentioning
confidence: 99%